MAKING E-GOVERNMENT WORK IN A SMART SOCIETY - Suranto, Suranto; Abdul Manaf, Halimah binti; Mutiarin, Dyah (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2025)
This study employed a bibliometric approach to examine the evolution of e-government research in the context of a smart society in Asia and Europe. E-government is essential for transforming public services; however, it faces obstacles, including the digital divide, data security, and challenges related to citizen engagement. This study used bibliometric analysis of the SCOPUS database to identify research trends, conceptual interrelationships, and thematic developments in e-government and smart society research from 2002 to 2025. The results demonstrated that incorporating smart city principles into e-government has expanded research to encompass governmental openness, civic engagement, and digital innovation. Nonetheless, a substantial disparity persists in the accessibility of digital services, especially for those with limited digital literacy. Moreover, significant disparities in e-government deployment are evident between industrialized and developing nations, shaped by legislation, infrastructural preparedness, and socio-economic conditions. This study offers insights into prospective research avenues and policy recommendations to improve the efficacy of e-government in fostering an inclusive and sustainable smart society.